Solid oxide fuel cell, solid oxide fuel cell stack, and method for manufacturing a solid oxide fuel cell
Patent Information
- Application Number
- JP2022509250
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2020-11-25
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2040-11-25
AI Technical Summary
【0015】 本発明によれば、カソード層が剥がれるのを抑制することが可能となる。
Smart Images

Figure 0007629444000001 
Figure 0007629444000002 
Figure 0007629444000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid oxide fuel cell, a solid oxide fuel cell stack, and a method for manufacturing a solid oxide fuel cell. [Background technology]
[0002] A solid oxide fuel cell has a structure in which a solid oxide electrolyte layer is provided between an anode layer and a cathode layer, and electricity is generated by reacting hydrogen in the fuel gas with oxide ions supplied from the cathode layer in the anode layer. The anode layer, cathode layer, and electrolyte layer are each made of ceramics and are vulnerable to sudden temperature changes and mechanical shocks.
[0003] Therefore, a structure called a metal-supported cell has been proposed, in which a solid oxide fuel cell is supported by a conductive support made of sintered metal, enabling the solid oxide fuel cell to withstand sudden temperature changes and mechanical shocks. The support in a metal-supported cell also functions as a current collector on the anode side, and current can be taken out to the outside through the support.
[0004] On the other hand, since materials commonly used for the cathode layer are difficult to sinter in a reducing atmosphere, the cathode layer is formed by sintering a ceramic material in an air atmosphere. However, if the sintering temperature of the cathode layer is high, the support is oxidized, and the conductivity of the support is reduced.
[0005] Therefore, a method has been proposed in which the cathode layer is fired in an air atmosphere at a low temperature of 1000° C. or less to suppress oxidation of the support (Non-Patent Documents 1 and 2). However, firing the cathode layer at such a low temperature may cause the cathode layer to peel off from the base such as the electrolyte layer. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] ECS Transactions, 25(2) 701-710 (2009) [Non-Patent Document 2] Journal of Power Sources 196 (2011) 9459-9466 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the above-mentioned problems, and aims to provide a solid oxide fuel cell, a solid oxide fuel cell stack, and a method for manufacturing a solid oxide fuel cell that are capable of suppressing peeling of a cathode layer. [Means for solving the problem]
[0008] The solid oxide fuel cell according to the present invention comprises a support mainly made of metal, an anode layer supported by the support, a solid oxide electrolyte layer provided on the anode layer, a cathode layer provided on the electrolyte layer and having oxide ion conductivity, and a metal porous layer covering the cathode layer and the electrolyte layer around the cathode layer. The metal porous layer is in close contact with the electrolyte layer. The present invention is characterized by the above.
[0009] In the solid oxide fuel cell, the voids may occupy 20% or more of the total area of the voids and metal appearing in a cross section of the porous layer.
[0010] In the solid oxide fuel cell, the metal of the porous layer may include silver.
[0011] In the above solid oxide fuel cell, the metal of the porous layer may include any of gold, platinum, palladium, and a silver-palladium alloy.
[0012] In the solid oxide fuel cell, the porous layer may have a thickness of 5 μm or more.
[0013] The solid oxide fuel cell stack according to the present invention comprises a first support mainly made of metal, a first anode layer supported by the first support, a first electrolyte layer made of a solid oxide having oxide ion conductivity and provided on the first anode layer, a first cathode layer provided on the first electrolyte layer, a first porous layer made of metal covering the first cathode layer and the first electrolyte layer around the first cathode layer, a first surface connected to the first porous layer, and a second surface opposite to the first surface. an anode current collector connected to the second surface of the interconnector; a second support provided on the anode current collector; a second anode layer supported by the second support; a second electrolyte layer made of a solid oxide having oxide ion conductivity provided on the second anode layer; a second cathode layer provided on the first electrolyte layer; and a second porous layer made of a metal covering the second cathode layer and the second electrolyte layer around the first cathode layer, the first porous layer of metal is in intimate contact with the first electrolyte layer, and the second porous layer of metal is in intimate contact with the second electrolyte layer; The interconnector is characterized in that a first recess is formed on the first surface thereof, the first recess being open to the first porous layer side and forming a first gas flow path between the first porous layer and the first recess, and a second recess is formed on the second surface thereof, the second recess being open to the anode current collector side and forming a second gas flow path between the anode current collector and the second recess.
[0014] The method for producing a solid oxide fuel cell according to the present invention is characterized by comprising the steps of: preparing a laminate in which a support mainly composed of a metal, an anode layer, and an electrolyte layer made of a solid oxide having oxide ion conductivity are laminated in that order; applying a slurry containing a conductive ceramic powder onto the electrolyte layer; forming a cathode layer by firing the slurry at a temperature of 1000°C or less in an oxidizing atmosphere; applying a paste containing an organic material and a metal powder so as to cover the cathode layer and the electrolyte layer surrounding the cathode layer; and forming a porous metal layer by firing the paste to remove the organic material. Effect of the Invention
[0015] According to the present invention, it is possible to suppress peeling of the cathode layer. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view illustrating a stack structure of a solid oxide fuel cell according to a first embodiment. [Diagram 2] This is a diagram based on a SEM (Scanning Electron Microscope) image of a cross section of a porous layer. [Diagram 3] FIG. 2 is an enlarged cross-sectional view illustrating details of the support, the mixed layer and the anode layer. [Figure 4] FIG. 2 is a diagram illustrating a flow of a method for manufacturing a fuel cell. [Diagram 5] 1 is a table summarizing the results of Example 1, Example 2, Comparative Example 1, and Comparative Example 2. [Figure 6] FIG. 5 is a schematic cross-sectional view of a solid oxide fuel cell stack according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment will be described with reference to the drawings. (First embodiment) Fig. 1 is a schematic cross-sectional view illustrating the layered structure of a solid oxide fuel cell 100 according to the first embodiment. As illustrated in Fig. 1, the fuel cell 100 has a structure in which a mixed layer 20, an anode layer 30, an electrolyte layer 40, a cathode layer 60, and a porous layer 70 are layered in this order on a support 10. A plurality of fuel cells 100 may be layered to form a fuel cell stack.
[0018] The electrolyte layer 40 is a dense layer that is mainly composed of a solid oxide having oxide ion conductivity and is gas impermeable. The electrolyte layer 40 is preferably mainly composed of scandia-yttria stabilized zirconium oxide (ScYSZ) or the like. The oxide ion conductivity is highest when the concentration of Y2O3+Sc2O3 is between 6 mol% and 15 mol%, and it is desirable to use a material with this composition. The thickness of the electrolyte layer 40 is preferably 20 μm or less, and more desirably 10 μm or less. The thinner the electrolyte, the better, but in order to manufacture the electrolyte so that gas does not leak from both sides, a thickness of 1 μm or more is desirable.
[0019] The cathode layer 60 is an electrode having electrode activity as a cathode, and has electronic conductivity and oxide ion conductivity. For example, the cathode layer 60 is LSC (lanthanum strontium cobaltite) having electronic conductivity and oxide ion conductivity. LSC is LaCoO3 doped with Sr (strontium).
[0020] In addition, a reaction prevention layer 50 is provided on the upper surface of the electrolyte layer 40. The reaction prevention layer 50 is mainly composed of a component that prevents a reaction between the electrolyte layer 40 and the cathode layer 60. For example, the reaction prevention layer 50 is mainly composed of GDC (Gd-doped ceria) in which Gd (gadolinium) is doped into CeO2. As an example, when the electrolyte layer 40 contains ScYSZ and the cathode layer 60 contains LSC, the reaction prevention layer 50 prevents the following reactions. Sr+ZrO2 → SrZrO3 La+ZrO3→La2Zr2O7
[0021] The porous layer 70 is a silver porous layer that prevents the cathode layer 60 from peeling off from the base. In this example, the porous layer 70 is formed to cover the cathode layer 60 and the electrolyte layer 40 in the surrounding region R. According to this structure, the porous layer 70 adheres to the electrolyte layer 40 in the region R via the reaction prevention layer 50, so that the cathode layer 60 is pressed down by the porous layer 70 from above, and peeling of the cathode layer 60 from the electrolyte layer 40 can be suppressed. Furthermore, oxygen flows through a plurality of voids contained in the porous layer 70, so that oxygen can be supplied to the cathode layer 60 through the porous layer 70. In particular, silver contained in the porous layer 70 has good adhesion to ceramics among metals, so it is effective in suppressing peeling of the cathode layer 60. The material of the porous layer 70 is not limited to silver as long as it is a metal, and the porous layer 70 may be formed of any of gold, platinum, palladium, and a silver-palladium alloy. These metals are preferable because they can be sintered in air and have good electrical conductivity.
[0022] The thickness of the porous layer 70 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The reason why the thickness of the porous layer 70 is set to 5 μm or more is that if the thickness is thinner than this, the force with which the porous layer 70 presses the cathode layer 60 against the electrolyte layer 40 becomes weak, and the cathode layer 60 may peel off from the electrolyte layer 40. On the other hand, if the porous layer 70 is formed to a thickness of 5 μm or more, the porous layer 70 can sufficiently press the cathode layer 60 against the electrolyte layer 40, and the porous layer 70 can be prevented from peeling off from the electrolyte layer 40.
[0023] On the other hand, the thickness of the porous layer 70 is preferably 100 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less. The reason for setting the upper limit at 100 μm or less is that if the porous layer 70 is made thicker than this, the oxygen gas diffusion resistance on the cathode side increases, resulting in a deterioration of the characteristics.
[0024] FIG. 2 is a diagram based on a scanning electron microscope (SEM) image of the cross section of the porous layer 70. As shown in FIG. 2, many voids are formed in the porous layer 70. If the voids are too small, oxygen does not easily flow through the voids, and it becomes difficult to supply oxygen to the cathode layer 60. In order to efficiently supply oxygen to the cathode layer 60, it is preferable that the voids occupy 20% or more of the total area S of the voids and silver that appear in the cross section of the porous layer 70. Furthermore, by making the voids occupy 30% or more, more preferably 40%, of the total area S, oxygen can be easily supplied to the cathode layer 60, and the power generation efficiency of the fuel cell 100 can be improved. The ratio of the area of the voids to the total area S of the voids and silver is hereinafter referred to as the porosity. The porosity is calculated by taking photographs of five or more locations on a cross-sectional SEM image of the sample (e.g., Figure 2) at a magnification sufficient to confirm the entire thickness of the porous layer 70, and calculating the average ratio of the void area estimated from the photographs to the total area.
[0025] Furthermore, the ratio of the area occupied by voids to the total area S of the voids and silver appearing in the cross section of the porous layer 70 is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less. The reason why the upper limit of the porosity is set at 90% is that if the porosity is greater than this, the strength of the porous layer 70 will be weakened, making it difficult to prevent peeling of the cathode layer 60.
[0026] Fig. 3 is an enlarged cross-sectional view illustrating the details of the support 10, the mixed layer 20, and the anode layer 30. As illustrated in Fig. 3, the support 10 is a member that has gas permeability and is capable of supporting the mixed layer 20, the anode layer 30, the electrolyte layer 40, the reaction prevention layer 50, and the cathode layer 60. The support 10 is a metal porous body, such as a porous body of an Fe-Cr alloy.
[0027] The anode layer 30 is an electrode having electrode activity as an anode, and has an electrode skeleton of a ceramic material. The electrode skeleton does not contain metal components. In this configuration, the decrease in the porosity of the anode layer 30 caused by the coarsening of the metal components during firing in a high-temperature reducing atmosphere is suppressed. In addition, alloying with the metal components of the support 10 is suppressed, and the decrease in catalytic function is suppressed.
[0028] The electrode skeleton of the anode layer 30 preferably has electronic conductivity and oxide ion conductivity. The anode layer 30 preferably contains a first oxide 31 as an electronically conductive material. As the first oxide 31, for example, a perovskite oxide having a composition formula represented by ABO3, in which the A site is at least one selected from the group consisting of Ca, Sr, Ba, and La, and the B site contains at least Cr, can be used. This perovskite oxide has good electronic conductivity. The molar ratio of the A site to the B site may be B≧A. Specifically, as the first oxide 31, a LaCrO3-based material or the like can be used.
[0029] In addition, the electrode skeleton of the anode layer 30 preferably contains the second oxide 32 as an oxide ion conductive material. The second oxide 32 is ScYSZ or the like. For example, it is preferable to use ScYSZ having a composition range of 5 mol% to 16 mol% of scandia (Sc2O3) and 1 mol% to 3 mol% of yttria (Y2O3). ScYSZ with a total amount of scandia and yttria added of 6 mol% to 15 mol% is more preferable. This is because the oxide ion conductivity is highest in this composition range. Note that the oxide ion conductive material is, for example, a material with an oxide ion transport number of 99% or more. GDC or the like may be used as the second oxide 32. In the example of FIG. 3, the same solid oxide as the solid oxide contained in the electrolyte layer 40 is used as the second oxide 32.
[0030] As illustrated in FIG. 3, in the anode layer 30, for example, a first oxide 31 and a second oxide 32 form an electrode skeleton. This electrode skeleton forms a plurality of voids. A catalyst is supported on the surface of the electrode skeleton in the void portion. Therefore, in the electrode skeleton formed in a spatially continuous manner, a plurality of catalysts are arranged in a spatially dispersed manner. It is preferable to use a composite catalyst as the catalyst. For example, it is preferable that a third oxide 33 having oxide ion conductivity and a catalytic metal 34 are supported on the surface of the electrode skeleton as the composite catalyst. For example, Y-doped BaCe 1-x Zr x O3(BCZY, x=0~1), Y-doped SrCe 1-x Zr x O3 (SCZY, x=0-1), Sr-doped LaScO3 (LSS), GDC, etc. can be used. Ni, etc. can be used as the catalytic metal 34. The third oxide 33 may have the same composition as the second oxide 32, or may have a different composition. The metal functioning as the catalytic metal 34 may be in the form of a compound when power generation is not yet performed. For example, Ni may be in the form of NiO (nickel oxide). These compounds are reduced by a reducing fuel gas supplied to the anode layer 30 during power generation, and take the form of a metal functioning as an anode catalyst.
[0031] The mixed layer 20 contains a metal material 21 and a ceramic material 22. In the mixed layer 20, the metal material 21 and the ceramic material 22 are randomly mixed. Therefore, a structure in which a layer of the metal material 21 and a layer of the ceramic material 22 are laminated is not formed. A plurality of voids are also formed in the mixed layer 20. The metal material 21 is not particularly limited as long as it is a metal. In the example of FIG. 3, the same metal material as that of the support 10 is used as the metal material 21. The first oxide 31, the second oxide 32, etc. can be used as the ceramic material 22. For example, ScYSZ, GDC, SrTiO3-based material, LaCrO3-based material, etc. can be used as the ceramic material 22. Since the SrTiO3-based material and the LaCrO3-based material have high electronic conductivity, the ohmic resistance in the mixed layer 20 can be reduced.
[0032] The fuel cell 100 generates power by the following actions. An oxidant gas containing oxygen, such as air, is supplied to the cathode layer 60. In the cathode layer 60, the oxygen that has reached the cathode layer 60 reacts with electrons supplied from an external electric circuit to become oxide ions. The oxide ions move to the anode layer 30 side through the electrolyte layer 40. Meanwhile, a fuel gas containing hydrogen, such as hydrogen gas or reformed gas, is supplied to the support 10. The fuel gas reaches the anode layer 30 through the support 10 and the mixed layer 20. The hydrogen that has reached the anode layer 30 releases electrons in the anode layer 30 and reacts with oxide ions that have been conducted through the electrolyte layer 40 from the cathode layer 60 side to become water (H2O). The released electrons are taken out by the external electric circuit. The electrons taken out are supplied to the cathode layer 60 after performing electrical work. Power is generated by the above actions.
[0033] In the above power generation reaction, the catalytic metal 34 functions as a catalyst in the reaction between hydrogen and oxide ions. The first oxide 31 is responsible for the conduction of electrons obtained by the reaction between hydrogen and oxide ions. The second oxide 32 is responsible for the conduction of oxide ions that reach the anode layer 30 from the electrolyte layer 40.
[0034] Furthermore, the fuel cell 100 according to this embodiment has a structure that is resistant to thermal shock, mechanical shock, etc., since it includes the support 10 whose main component is metal. A method for manufacturing the fuel cell 100 will be described below. Figure 4 is a diagram illustrating a flow of the method for manufacturing the fuel cell 100.
[0035] (Process for preparing support material) The support material is made into a slurry by mixing metal powder (for example, particle size 10 μm to 100 μm), plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), dissipation material (organic matter), and binder (PVB, acrylic resin, ethyl cellulose, etc.). The support material is used as a material for forming the support 10. The volume ratio of the organic components (dissipation material, binder solids, plasticizer) to the metal powder is, for example, in the range of 1:1 to 20:1, and the amount of the organic components is adjusted depending on the porosity.
[0036] (Preparation process of materials for mixed layer) As the material for the mixed layer, ceramic material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the ceramic material 22, metal material powder with a small particle size (for example, particle size 1 μm to 10 μm) which is the raw material of the metal material 21, solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), vanishing material (organic matter), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic component (vanishing material, binder solid content, plasticizer) to the ceramic material powder and metal material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic component is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the vanishing material. The ceramic material powder may contain an electron conductive material powder and an oxide ion conductive material powder. In this case, the volume ratio of the electron conductive material powder to the oxide ion conductive material powder is preferably in the range of, for example, 1:9 to 9:1. Also, even if an electrolyte material such as ScYSZ or GDC is used instead of the electron conductive material, there is no peeling at the interface, and a cell can be fabricated. However, from the viewpoint of reducing the ohmic resistance, it is preferable to mix the electron conductive material with a metal powder.
[0037] (Preparation process of anode layer material) As the material for the anode layer, a ceramic material powder constituting the electrode skeleton, a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), a dissipating material (organic material), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. As the ceramic material powder constituting the electrode skeleton, an electron conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the first oxide 31, an oxide ion conductive material powder (for example, particle size 100 nm to 10 μm) which is the raw material of the second oxide 32, etc. may be used. The volume ratio of the organic component (dissipating material, binder solid content, plasticizer) to the electron conductive material powder is, for example, in the range of 1:1 to 5:1, and the amount of the organic component is adjusted depending on the porosity. The pore size of the voids is controlled by adjusting the particle size of the dissipating material. The volume ratio of the electron conductive material powder to the oxide ion conductive material powder is set to a range of 3:7 to 7:3, for example.
[0038] (Electrolyte layer material manufacturing process) As the material for the electrolyte layer, oxide ion conductive material powder (e.g., ScYSZ, YSZ, GDC, etc., with a particle size of 10 nm to 1000 nm), solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., 20 wt% to 30 wt% depending on the viscosity), plasticizer (e.g., adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), and binder (PVB, acrylic resin, ethyl cellulose, etc.) are mixed to form a slurry. The volume ratio of the organic components (binder solids, plasticizer) to the oxide ion conductive material powder is, for example, in the range of 6:4 to 3:4.
[0039] (Preparation process of cathode layer material) The cathode layer material is prepared by mixing conductive ceramic powder such as lanthanum strontium cobaltite (LSC: LaSrCoO3) with a solvent (toluene, 2-propanol (IPA), 1-butanol, terpineol, butyl acetate, ethanol, etc., at 20 wt% to 30 wt% depending on the viscosity), a plasticizer (for example, adjusted to 1 wt% to 6 wt% to adjust the adhesion of the sheet), and a binder (PVB, acrylic resin, ethyl cellulose, etc.) to form a slurry. The volume ratio of the organic components (binder solids, plasticizer) to the LSC powder is, for example, in the range of 6:4 to 1:4.
[0040] (Firing process) First, a support material is applied onto a PET (polyethylene terephthalate) film to prepare a support green sheet. A mixed layer material is applied onto another PET film to prepare a mixed layer green sheet. An anode layer material is applied onto another PET film to prepare an anode layer green sheet. An electrolyte layer green sheet is applied onto another PET film to prepare an electrolyte layer green sheet. For example, multiple support green sheets, one mixed layer green sheet, one anode layer green sheet, and one electrolyte layer green sheet are laminated in this order, cut to a predetermined size, and then heated at a temperature of 10°C until the oxygen partial pressure reaches 10°C. -20 The mixture is fired in a reducing atmosphere of 1 atm or less at a temperature range of about 1100° C. to 1300° C. Thereby, a laminate in which the support 10, the mixed layer 20, the electrode skeleton of the anode layer 30, and the electrolyte layer 40 are laminated in this order can be obtained.
[0041] (Impregnation process) Next, the raw materials of the third oxide 33 and the catalytic metal 34 are impregnated into the electrode skeleton of the anode layer 30. For example, nitrates or chlorides of Zr, Y, Sc, Ce, Gd, and Ni are dissolved in water or alcohols (ethanol, 2-propanol, methanol, etc.) so that Gd-doped ceria or Sc, Y-doped zirconia and Ni are produced when fired at a predetermined temperature in a reducing atmosphere, and the half cell is impregnated, dried, and the heat treatment is repeated as many times as necessary.
[0042] (Reaction prevention layer forming process) The reaction prevention layer 50 is formed by, for example, PVD. 0.8 Gd 0.2 O 2-x can be formed into a film having a thickness of 1 μm.
[0043] (Cathode layer formation process) Next, a slurry of cathode material is applied onto the reaction prevention layer 50 by screen printing or the like, and dried. The slurry is then sintered at a temperature of 1000°C or less in an oxidizing atmosphere such as an air atmosphere to form the cathode layer 60. In order to prevent the metal contained in the support 10 from being oxidized, it is preferable to perform this heat treatment at a temperature of 900°C or less. Furthermore, by performing this heat treatment at a temperature of 800°C or less, oxidation of the metal contained in the support 10 can be effectively suppressed.
[0044] (Porous layer formation process) Next, a silver paste made by mixing silver powder with an organic material (PVB, acrylic resin, ethyl cellulose, etc.) for creating voids is printed on the cathode layer 60. The silver paste is printed over an area larger than the area of the cathode layer 60 so that the entire cathode layer 60 is covered with the silver paste. Thereafter, the silver paste is subjected to a heat treatment at a temperature of 800° C. in an air atmosphere. This heat treatment causes the organic material to be desorbed from the silver paste, and a porous layer 70 having a plurality of voids is formed. Through the above steps, the fuel cell 100 can be produced. Note that instead of the silver paste, a paste containing a metal powder of any of gold, platinum, palladium, and a silver-palladium alloy may be used. EXAMPLES
[0045] A fuel cell 100 was produced according to the manufacturing method according to the above embodiment. Example 1 The material of the cathode layer 60 is La 0.8 Sr 0.2A LaCoO3-based material in which CoO3 is doped with Sr was used. A silver porous layer 70 was then formed on the cathode layer 60. The area of the porous layer 70 was made larger than the area of the cathode layer 60 so that the entire cathode layer 60 was covered with the porous layer 70. The fuel cell 100 was made to generate power and the resistance values of each part were separated by impedance measurement. As a result, the ohmic resistance of the cathode layer 60 was 0.25 Ω cm 2 The reaction resistance of the cathode layer 60 is 0.27 Ω cm 2 It was. The thickness of the porous layer 70 was 20 μm. The ratio of the area occupied by the voids to the total area of the voids and silver appearing in the cross section of the porous layer 70 was 40%.
[0046] Furthermore, when the surface of the fuel cell 100 after power generation was observed with an optical microscope, there was no sign of peeling of the cathode layer 60. Furthermore, when the cross section was observed with an SEM, there was no peeling between the cathode layer 60 and the electrolyte layer 40. Although the cathode layer 60 is somewhat deformed when the fuel cell 100 is operated to generate power, it is believed that peeling of the cathode layer 60 due to deformation did not occur because the cathode layer 60 is pressed down from above by the porous layer 70.
[0047] Example 2 As in Example 1, the material of the cathode layer 60 was La 0.8 Sr 0.2 A LaCoO3-based material in which CoO3 is doped with Sr was used. A silver porous layer 70 was then formed on the cathode layer 60. The area of the porous layer 70 was made larger than the area of the cathode layer 60, so that the entire cathode layer 60 was covered with the porous layer 70.
[0048] Furthermore, in this embodiment, a metal mesh was placed on the porous layer 70 as a current collector, and this current collector was used to press the porous layer 70 against the cathode layer 60. In this state, the fuel cell 100 was set on a power generation jig. The fuel cell 100 was then made to generate power, and the resistance values of each part were measured by impedance measurement. As a result, the ohmic resistance of the cathode layer 60 was found to be 0.25 Ω cm2 The reaction resistance of the cathode layer 60 is 0.27 Ω cm 2 These values are the same as those in Example 1. Therefore, it was revealed that even when no current collector is used as in Example 1, the resistance of each part can be reduced to the same extent as when a current collector is used as in Example 2.
[0049] Furthermore, when the surface of the fuel cell 100 after power generation was examined with an optical microscope, no peeling of the cathode layer 60 was found. Furthermore, when the cross section was observed with an SEM, no peeling was found between the cathode layer 60 and the electrolyte layer 40.
[0050] Comparative Example 1 As in Example 1, the material of the cathode layer 60 was La 0.8 Sr 0.2 A LaCoO3-based material in which Sr is doped into CoO3 was used. However, unlike Example 1, the porous layer 70 was not formed on the cathode layer 60. Instead of the porous layer 70, a metal mesh was placed as a current collector on the cathode layer 60, and this current collector was used to press the cathode layer 60 against the electrolyte layer 40. In this state, the fuel cell 100 was set on a power generation jig. The fuel cell 100 was then made to generate power, and the resistance values of each part were separated by impedance measurement. As a result, the ohmic resistance of the cathode layer 60 was 0.43 Ω cm 2 The reaction resistance of the cathode layer 60 is 1.23 Ω cm 2 These values are all larger than those in the first embodiment.
[0051] In addition, when the surface of the fuel cell 100 after power generation was observed with an optical microscope, cracks were found on the surface of the cathode layer 60, and peeling of the cathode layer 60 occurred due to the cracks. When the electrolyte layer 40 under the peeled cathode layer 60 was observed, it was found that the electrolyte layer 40 was glossy and that the adhesion between the electrolyte layer 40 and the cathode layer 60 was poor. Furthermore, as a result of observing the cross section with an SEM, it was confirmed that the cathode layer 60 had peeled off from the electrolyte layer 40. This is thought to be because the cathode layer 60 was not covered with the porous layer 70, and the cathode layer 60 was peeled off from the electrolyte layer 40 only due to slight deformation of the cathode layer 60 during power generation. Furthermore, it is thought that the peeling of the cathode layer 60 caused both the ohmic resistance and the reaction resistance to show very high values as described above.
[0052] Comparative Example 2 As in Comparative Example 1, the material of the cathode layer 60 was La 0.8 Sr 0.2 A LaCoO3-based material in which CoO3 was doped with Sr was used. No porous layer 70 was formed on the cathode layer 60. Also, unlike Comparative Example 1, in this Comparative Example, no metal mesh current collector was placed on the cathode layer 60. In this state, the fuel cell 100 was set on a power generation jig, and the fuel cell 100 was made to generate power. The resistance values of each part during power generation were separated by impedance measurement, and the ohmic resistance of the cathode layer 60 was found to be 0.72 Ω cm 2 The reaction resistance of the cathode layer 60 is 1.2 Ω cm 2 These values are all larger than those in the first embodiment.
[0053] Furthermore, when the surface of the fuel cell 100 after power generation was observed with an optical microscope, cracks were found to have occurred on the surface of the cathode layer 60, and further peeling of the cathode layer 60 occurred over a wide area. When the electrolyte layer 40 below the peeled cathode layer 60 was observed in the same manner as in Comparative Example 2, it was found that the electrolyte layer 40 was glossy, and that the adhesion between the electrolyte layer 40 and the cathode layer 60 was poor. Furthermore, as a result of observing the cross section with an SEM, it was confirmed that the cathode layer 60 had peeled off from the electrolyte layer 40.
[0054] In this comparative example, since there is no current collector pressing the cathode layer 60 against the electrolyte layer 40, peeling occurs over a wide area of the cathode layer 60, which is thought to be the reason for the increase in the ohmic resistance of the cathode layer 60 as described above.
[0055] Fig. 5 is a table summarizing the results of the above-mentioned Example 1, Example 2, Comparative Example 1, and Comparative Example 2. As shown in Fig. 5, in Examples 1 and 2 in which the porous layer 70 is formed, peeling of the cathode layer 60 did not occur, and as a result, both the ohmic resistance and the reaction resistance had low values.
[0056] On the other hand, in Comparative Examples 1 and 2 in which the porous layer 70 was not formed, peeling of the cathode layer 60 occurred, and compared with Examples 1 and 2, the ohmic resistance and reaction resistance became larger values.
[0057] Second embodiment In this embodiment, a solid oxide fuel cell stack including a plurality of fuel cells will be described.
[0058] Fig. 6 is a schematic cross-sectional view of a solid oxide fuel cell stack according to the second embodiment. In Fig. 6, the same elements as those described in the first embodiment are denoted by the same reference numerals as in the first embodiment, and their description will be omitted below. As shown in Fig. 6, a fuel cell stack 200 has a first fuel cell 110 and a second fuel cell 120. These fuel cells 110, 120 are both solid oxide fuel cells and have the same structure as the fuel cell 100 according to the first embodiment.
[0059] An interconnect 130 is provided between the first fuel cell 110 and the second fuel cell 120 to electrically connect these fuel cells. The interconnect 130 has a first surface 130a connected to the porous layer 70 of the first fuel cell 110. A first recess 130x that is open to the porous layer 70 side of the first fuel cell 110 is formed on the first surface 130a, and a first flow path 141 is formed by the first recess 130x and the porous layer 70. The first flow path 141 is a flow path through which air flows, and oxygen in the air is supplied to the electrolyte layer 40 of the first fuel cell 110 via the porous layer 70.
[0060] The interconnect 130 also has a second surface 130b opposite to the first surface 130a. The second surface 130b is connected to the anode current collector 90, thereby electrically connecting the interconnect 130 to the second fuel cell 120. The anode current collector 90 is, for example, a metal mesh such as nickel bonded to the support 10 of the second fuel cell 120.
[0061] Furthermore, a second recess 130y that is open to the anode current collector 90 side is formed on the second surface 130b, and a second flow path 142 is formed by the second recess 130y and the anode current collector 90. The second flow path 142 is a flow path through which a fuel gas containing hydrogen flows, and the hydrogen is supplied to the second fuel cell 120 via the anode current collector 90.
[0062] According to such a fuel cell stack 200, since the porous layer 70 is formed in each fuel cell 110, 120 as described in the first embodiment, the cathode layer 60 below the porous layer 70 can be prevented from peeling off from the underlying electrolyte layer 40. [Explanation of symbols]
[0063] 10 Support 20 mixed layer 30 Anode layer 40 Electrolyte layer 50 Reaction prevention layer 60 Cathode layer 70 Porous Layer 100, 110, 120 fuel cell 200 Fuel Cell Stack
Claims
1. A support mainly composed of a metal; an anode layer supported by the support; a solid oxide electrolyte layer having oxide ion conductivity provided on the anode layer; a cathode layer disposed on the electrolyte layer; a porous metal layer covering the cathode layer and the electrolyte layer around the cathode layer; wherein the metal porous layer is in intimate contact with the electrolyte layer.
2. 2. The solid oxide fuel cell according to claim 1, wherein the voids occupy 20% or more of the total area of the voids and metal appearing in a cross section of the porous layer.
3. 3. The solid oxide fuel cell according to claim 1, wherein the metal of the porous layer contains silver.
4. 3. The solid oxide fuel cell according to claim 1, wherein the metal of the porous layer contains any one of gold, platinum, palladium, and a silver-palladium alloy.
5. 2. The solid oxide fuel cell according to claim 1, wherein the porous layer has a thickness of 5 [mu]m or more.
6. A first support mainly composed of a metal; a first anode layer supported by the first support; a first electrolyte layer formed of a solid oxide having oxide ion conductivity and disposed on the first anode layer; a first cathode layer disposed on the first electrolyte layer; a first porous layer of metal covering the first cathode layer and the first electrolyte layer around the first cathode layer; an interconnector having a first surface connected to the first porous layer and a second surface opposite to the first surface; an anode current collector connected to the second surface of the interconnect; a second support provided on the anode current collector; a second anode layer supported by the second support; and a second electrolyte layer formed of a solid oxide having oxide ion conductivity and disposed on the second anode layer; a second cathode layer disposed on the first electrolyte layer; and a second porous layer of metal covering the second cathode layer and the second electrolyte layer around the first cathode layer; the first porous layer of metal is in intimate contact with the first electrolyte layer, and the second porous layer of metal is in intimate contact with the second electrolyte layer; a first recess is formed on the first surface of the interconnector, the first recess being open to the first porous layer side and forming a first gas flow path between the first porous layer and the first recess; a second recess formed on the second surface of the interconnector, the second recess being open toward the anode current collector and forming a second gas flow path between the interconnector and the anode current collector.
7. A step of preparing a laminate by sequentially stacking a support mainly composed of a metal, an anode layer, and an electrolyte layer made of a solid oxide having oxide ion conductivity; applying a slurry containing a conductive ceramic powder onto the electrolyte layer; forming a cathode layer by firing the slurry at a temperature of 1000° C. or less in an oxidizing atmosphere; applying a paste containing an organic substance and a metal powder so as to cover the cathode layer and the electrolyte layer around the cathode layer; firing the paste to remove the organic matter, thereby forming a porous metal layer; 2. A method for producing a solid oxide fuel cell comprising the steps of:
Citation Information
Patent Citations
Fuel cell
JP2005310529A
Fuel cell
JP2015065151A
Electrochemical reaction single cell, and electrochemical reaction cell stack
JP2018133165A
Fuel battery cell stack
JP2019046708A